Reingeniería de los procesos de la empresa pollos Gusy sucursal El Valle de la ciudad de Loja.. - Loján Acaro, Livia Dianita (2016)
This research work has considered the general objective of making a reengineering in the company of "Chickens Gusy" of the city of Loja. To carry out this work, a research methodology was applied in the implementation of the various methods of the historical method, which made it possible to know when and how they started from different production processes in the company roasted chickens Chickens used Gusy The analytical method allowed distinguish different services procedures in general, the synthetic method, allowed to relate the different activities that occur in business 5 processes, the deductive method, allowed to distinguish valuable elements within the company related to all the steps that occur within it, the descriptive method, I used to watch all company facilities and all areas where different processes occur; while the techniques were applied a survey to all employees and workers of the company they are currently working; according to these results and observations and information obtained was found that procurement processes, safe, kitchen, barbecue and office, they did not properly, wasting time and exist a lack of coordination among different stages in the process, representing it is not agile and cause downtime mean losses for the company. The Manager of the Company, plus representatives of each of the process responsible for the research: For this a reengineering team, which aims to integrate it settled. To consider the application of this research to the reality of the company, the reengineering team would be responsible for analyzing the information obtained in the same, identify whether the processes identified in this investigation are sufficient; their problems and the proposed amendment. Through the mapping of processes it could clearly establish the time and distance of each process; and then the analysis allowed to determine the objectives, strategies redesigned processes indicated similarly with corresponding programs flows. Also, with this proposal reengineering, they have established new staff roles, the same as recorded in clear, in the operating functions for each of the positions of the processes that have been redesigned. It should be noted that the proposal process reengineering is able to reduce 188 minutes in all processes without involving a reduction in quality; and, as to the value of reengineering this it amounts to $ 2,826.14, which is very acceptable to the owners of the company. All results presented in this research note that it is possible a substantial improvement in the company and it would therefore be advisable to implement it. Among the most important conclusions we Chickens Gusy the company to apply the reengineering will allow reduce the time in some processes, it will remove unnecessary delay, establishing new times in different processes. With reengineering, the leaders of the processes have greater knowledge and process control, so they can target more accurately the activities of the company.